Virtual worlds in distance learning - Elena Fabiola Ruiz Ledesma; Jonathan Axel Cruz Vázquez; Lorena Chavarría Báez (International Journal of Evaluation and Research in Education (IJERE), 2022)
Virtual worlds are considered an additional proposal within the e-learning model. Online platforms have not been enough resources to be successful in the teaching and learning processes, therefore, it is necessary to search more options that contribute to their improvement. Virtual worlds, through inverse and visual experiences for the student, offer new panoramas that allow living situations and solving problems in different areas, such as mathematics. This article analyzes the opinion of higher-level students regarding the use of virtual worlds in their distance classes. Likewise, the virtual worlds provide help in improving teacher-student and student-student relationships. Some cases of educational institutions that integrated the use of virtual worlds into their classes are shown. A Likert-type scale questionnaire has been applied to a sample of 65 higher-level students. Its reliability was validated by means of Cronbach's alpha coefficients and Pearson's. It was found that students consider that the use of virtual worlds would improve class work and relationships between their peers and their teachers. It is remarkably undoubted that virtual worlds within education path are considered an excellent tool for e-learning. However, although the interest on the part of students is high, it is necessary to carry out more researching and developing procedures on the virtual worlds as an alternative to support learning.